DINAMIKA PERKEMBANGAN ILMU ISLAM DAN ILMU KEISLAMAN - Saiful Bahri (Pascasarjana UIN Sumatera Utara, 2021)
Science will always follow developments with the progress of science will create various conveniences for humans in life. If science in the context of Islamic epistemology can be achieved through three sources/tools; senses, mind, and heart, so in Western epistemology, scientific knowledge can only be achieved through the senses and reason. Therefore, none of Allah's creatures can achieve perfection and maturity in life without going through a process of science or education. So, simply that science in Islam has distinctive characteristics that are fundamentally different from the sciences developed in the West, both in terms of foundation, source, means, and methodology. In Islam, science has a solid foundation through the Qur'an and Sunnah, sourced from the physical and metaphysical realms, obtained through the senses, reason, and heart/intuitive. The scope of his knowledge is very broad, not only concerning worldly issues, but also related to ukhrawi problems.Science will always follow developments with the progress of science will create various conveniences for humans in life. If science in the context of Islamic epistemology can be achieved through three sources/tools; senses, mind, and heart, so in Western epistemology, scientific knowledge can only be achieved through the senses and reason. Therefore, none of Allah's creatures can achieve perfection and maturity in life without going through a process of science or education. So, simply that science in Islam has distinctive characteristics that are fundamentally different from the sciences developed in the West, both in terms of foundation, source, means, and methodology. In Islam, science has a solid foundation through the Qur'an and Sunnah, sourced from the physical and metaphysical realms, obtained through the senses, reason, and heart/intuitive. The scope of his knowledge is very broad, not only concerning worldly issues, but also related to ukhrawi problems..